What Ethical Leadership Means to Me: Asian, American, and European Perspectives - Resick, Christian J.; Martin, Gillian S.; Keating, Mary A.; Dickson, Marcus W.; Kwan, Ho Kwong; Peng, Chunyan (2011)
Despite the increasingly multinational nature of the workplace, there have been few studies of the convergence and divergence in beliefs about ethics-based leadership across cultures. This study examines the meaning of ethical and unethical leadership held by managers in six societies with the goal of identifying areas of convergence and divergence across cultures. More specifically, qualitative research methods were used to identify the attributes and behaviors that managers from the People’s Republic of China (the PRC), Hong Kong, the Republic of China (Taiwan), the United States (the U.S.), Ireland, and Germany attribute to ethical and unethical leaders. Across societies, six ethical leadership themes and six unethical leadership themes emerged from a thematic analysis of the open-ended responses. Dominant themes for ethical and unethical leadership for each society are identified and examined within the context of the core cultural values and practices of that society. Implications for theory, research, and management practice are discussed.
Keywords: Unethical leadership; Leadership; Ethics; Ethical Leadership; cross-cultural leadership